Online radicalization: an overview of the role the Internet plays in radicalization - McCurdy, Emmet (My University, 2021)
Radicalization is the transition into acceptance and approval of extremist beliefs and actions, including condoning or committing acts of violence. In recent decades, the internet has played a crucial role in the radicalization of extremists and terrorists, as well as facilitating radical groups' recruitment efforts. The present review briefly discusses what radicalization is and how it unfolds in a general sense, before exploring how the internet is involved in three kinds of radicalization. The first is the deliberate radicalization and recruitment of new members into formally organized extremist groups (e.g. white supremacist militias and radical Islamic terror groups), and the second is self-radicalization via the internet, wherein unstable, discontent, and/or disenfranchised individuals pursue increasingly radical ideas and communities online until they condone or commit acts of violence on their own, without formal membership into an organized group. The third type of radicalization explored is stochastic or probabilistic radicalization, in which individuals encounter seemingly or actually benign ideas, beliefs, and pundits online, and are slowly radicalized via increasingly bold and dramatic content being suggested by the recommendation algorithms of Google and Youtube. The review clarifies some distinctions between the three types, before a brief summary and discussion.
Keywords: radicalization; Internet